Development of Digital Competencies of Tourism Human Resources in the Era of the Industrial Revolution 4.0 - Tiara Sukma (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2026)
The rapid development of digital transformation has brought significant changes to the competency requirements of human resources, including in the tourism sector. This study aims to examine the development of digital competencies among tourism human resources in facing digital transformation. This research employs a qualitative approach using a literature study method through the exploration of various relevant scientific sources, such as national and international journals, books, and official publications. The findings indicate that digital competence is a crucial factor in enhancing the competitiveness of tourism human resources in the digital era. These competencies not only include technical skills in using technology but also abilities in data analysis, critical thinking, creativity, and adaptability to technological advancements. Digitalization has also encouraged a shift in workforce roles from routine-based jobs to more strategic and technology-oriented work. In the tourism industry, mastery of digital technologies such as online platforms, social media, reservation systems, and the utilization of artificial intelligence has become an essential element in improving service quality and tourist experiences. Therefore, the development of digital competencies must be carried out continuously through reskilling and upskilling efforts, supported by organizations that are adaptive to technological developments. Thus, the development of digital competencies among human resources has become a strategic aspect in maintaining the sustainability and competitiveness of the tourism sector amid the Industrial Revolution 4.0.